Dynamics of Relations between Christianity and Islam in Minahasa - Farno BA Gerung; Daniel C. Kambey; Max Ruindungan (International Journal of Education, Information Technology, and Others, 2021)
This research is to analyze and describe the dynamics of Christian and Islamic relations in Minahasa by examining the phenomenon of conflict at Perum Agape Tumaluntung. Data collection was carried out through observation, document study, in-depth interviews. This research shows that there has been a change in Christian-Islamic relations in Minahasa. The beginning of the meeting between Christianity and Islam went well, but as time went on tensions began to occur and escalated and culminated in the destruction of the Mushola at Perum Agape Tumaluntung, also showing that social interaction between Christians and Muslims in Tumaluntung was not going well. This can be seen in the exclusive social actions of Muslim communities while Christians are slow to face social change. Social integration is not formed when there are differences of opinion between Christians and Muslims about the rules / norms of building mosques. This research also shows how Christians should interact socially with followers of other religions according to the biblical perspective.